Epidemiology of Type 2 Diabetic Foot Problems and Predictive Factors for Amputation in China. (March 2015) - Jiang, Yufeng; Ran, Xingwu; Jia, Lijing; Yang, Chuan; Wang, Penghua; Ma, Jianhua; Chen, Bing; Yu, Yanmei; Feng, Bo; Chen, Lili; Yin, Han; Cheng, Zhifeng; et al.
To determine incidence and clinically relevant risk factors for diabetic amputation in a large cohort study of diabetic foot ulceration patients in China, we investigated a total of 669 diabetic foot ulceration patients, who were assessed at baseline for demographic information, medical and social history, peripheral neuropathy screening, periphery artery disease screening, assessment of nutritional status and diabetic control, physical examination including foot deformity in 15 Grade III-A hospitals. Of the 669 patients, 435 were male and 201 were female, with the mean age being 64.0 years. Of all patients, 110 had neuropathic ulcers, 122 had ischemic ulcers, 276 had neuroischemic ulcers, and 12 cases were unclassified. Wagner classification showed 61 cases were grade I, 216 cases grade II, 159 cases grade III, 137 cases grade IV, and 7 cases grade V. The overall amputation rate among diabetic foot patients was 19.03%, and major and minor amputation rates were 2.14% and 16.88%, respectively. By univariate analysis, statistically significant differences were found in smoking, rest pain, ulcer history, revascularization history, amputation history, gangrene, infection, Wagner grades, duration of diabetes, and postprandial blood glucose, aldehyde, total protein, globulin, albumin, white blood cell (WBC), hemoglobin, HbA1c, ulcer property, body mass index, as well as creatinine. Binary logistic regression model showed that increased WBC (odds ratio 1.25) and ulcer history (odds ratio 6.8) were associated with increased risks from diabetic foot ulcer to major amputation; increased duration of diabetes (odds ratio 1.004), WBC (odds ratio 1.102), infection (odds ratio 2.323), foot deformity (odds ratio 1.973), revascularization history (odds ratio 2.662), and decreased postprandial blood sugar (odds ratio 0.94) were associated with increased risks from diabetic foot ulcer to minor amputation. It is of great importance to give better management to diabetic patients at early stages. Following a diagnosis of DFU more intensive surveillance and aggressive care may improve outcome.